Combined effect of inlet air cooling and fouling on performance of variable geometry industrial gas turbines - Hashmi, M.B. (Elsevier B.V., 2020)
The performance of industrial gas turbines is closely tied to the intake air temperature and component performance degradation caused by fouling, erosion, and foreign object damage (FOD). Generally, under hot and humid conditions an increase in the ambient intake air temperature induces a decline in gas turbines performance. With this regard, inlet air cooling (IAC) is an established technique that has been applied to reverse the deteriorating effects of high air temperatures. In this study, a steady-state off-design model for a single-shaft industrial gas turbine (Taurus 70) with a variable geometry has been developed to analyze a cumulative effect of fouling and variable ambient conditions on gas turbines performance. The validation of GasTurb 12, simulations was achieved by comparing the results with the Solar Turbines product catalog. The study has been segregated into four different scenarios: (i) with inlet air cooling, (ii) without inlet air cooling, (iii) with Variable Inlet Guide Vane (VIGV) schedule, and (iv) without VIGV schedule. With an increase in fouling severity level, thermal efficiency and specific fuel consumption (SFC) showed clear deterioration. However, with the integration of the IAC technique, the thermal efficiency and SFC improved that translate into economic gain. A novel idea has also been explored to investigate the effect of VIGV scheduling on performance improvement. It is observed that the deployment of the VIGV schedule improves the thermal efficiency and SFC that were previously deteriorating due to fouling. Hence, it is concluded that the integration of inlet air cooling with variable geometry engine can improve the performance of industrial gas turbines especially in hot climate regions such as the Middle East and Southeast Asian countries. Â© 2020 Faculty of Engineering, Alexandria University